Takayasu arteritis presenting as cerebral aneurysms in an 18 month old: A case report - Finkel Terri H; Pollock Avrum N; Corao Diana A; Weiss Pamela F; Smith Sabrina E (BMC, 2008)
Abstract Background Central nervous system involvement occurs in as many as twenty percent of Takayasu arteritis cases. When central nervous system disease is present, it typically manifests as cerebral ischemia or stroke. There are rare reports of intracranial aneurysms in adults with Takayasu arteritis, but none in children. Case presentation We describe a case of Takayasu arteritis in an 18 month old girl who presented with a ruptured cerebral aneurysm. Full body magnetic resonance angiography revealed bilateral iliac, pelvic and intragluteal aneurysms, irregular terminal aorta, and stenotic renal arteries. Iliac vessel biopsy showed a lymphocytic infiltrate and giant cells localized to the internal elastica. Conclusion This case highlights cerebral aneurysm as a highly unusual initial manifestation of Takayasu arteritis and demonstrates the challenges of diagnosis, treatment, and assessment of response to therapy in TA in children.